PENGARUH IMPLEMENTASI PROGRAM KEMITRAAN PT TELKOM TERHADAP PEMBERDAYAAN USAHA KECIL DI KOTA BANDUNG - Dadang Tahyu (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2011)
Small entrepreneurs have a significant role in national economy which has contributed on providing job oppotunities and enormous input to gross national product. Otherwise, small entrepreneurs still deal with some basic problems such as entrepreneurship capacity and business climate and competetion. Government has implement several policies conducted empowerment of small entrepreneurs. One of those policies is partnership program of national companies owned bygovernment. In fact, the implementation of program has not significantly supported a condusive business to small entrepreneurs. PT Telkom as a national companies which is implementing partnership program that well-known byachieving some outstanding success in partnershi program. However, PT Telkom still are not able to implement the program optimally based on its regulations.This research is aimed to analize the influence of partnership program implementation of PT. Telkom toward small entrepreneur empowerment in Bandung City. The theory was applied with model of public policyimplementation by Edward III (1978) and empowerment theory by Ambar T.S. (2004). The research used explanatory survey method. The result shows that the partnership program implementation of PT. Telkom that containing; bureaucraticstructure, resources, disposition and communication has significant influence toward small entrepreneur empowerment in Bandung City.